Efficacy of Sacubitril/Valsartan Sodium Combined with Simvastatin in Treating Chronic Heart Failure with Arrhythmia and Its Effects on IL-6, IL-8, and TNF-α: Sacubitril/Valsartan and Simvastatin in Heart Failure with Arrhythmia - Li, Jingjing; Wang, Zhihua (Journal of Medical Biochemistry, 2025)
Background: To explore, in conjunction with clinical practice, the efficacy of different pharmacological treatment regimens for patients with chronic heart failure complicated by arrhythmia, and their effects on inflammatory factor levels. Methods: A total of 96 patients with chronic heart failure and arrhythmia treated at our hospital from June 2022 to January 2025 were selected and randomly assigned by envelope method into a combination therapy group and a simvastatin group. The simvastatin group received simvastatin monotherapy, while the combination group was treated with sacubitril/valsartan sodium plus simvastatin. Clinical efficacy was compared between the two groups. Cardiac function, inflammatory factors, arrhythmia episodes, blood lipid levels, and oxidative stress markers were assessed before and after treatment. Adverse reactions in both groups were also observed. Results: The overall effective rate in the combination therapy group (93.75%) was significantly higher than that in the simvastatin group (72.92%) (χ2=7.500, P=0.006). After treatment, the combination group exhibited higher LVEF and lower LVESD and LVEDD levels compared to the simvastatin group (P<0.05). Serum levels of inflammatory factors (IL-6, IL-8, TNF-α) were significantly lower in the combination group than in the simvastatin group after treatment (P<0.05). Both the duration and frequency of arrhythmia episodes were reduced in the combination group compared to the simvastatin group (P<0.05). Post-treatment, LDL-C, TG, and TC levels were lower, and HDL-C was higher in the combination group than in the simvastatin group (P<0.05). MDA and SOD levels were also lower in the combination group after treatment (P<0.05). The incidence of adverse reactions was lower in the combination group (3.33%) compared to the simvastatin group (22.92%) (χ2=5.352, P=0.021). Conclusion: For patients with chronic heart failure and arrhythmia, combined therapy with sacubitril/valsartan sodium and simvastatin demonstrates significant efficacy. It can alleviate inflammatory responses, improve cardiac function, reduce the frequency and duration of arrhythmia episodes, optimize lipid profiles and stress responses, and decrease adverse reactions. This approach is worthy of further clinical promotion.